Cold Pulsatile Machine Perfusion versus Static Cold Storage in Kidney Transplantation: A Single Centre Experience. (16th January 2019) - Bellini, Maria Irene; Charalampidis, Sotiris; Herbert, Paul Elliot; Bonatsos, Vasileios; Crane, Jeremy; Muthusamy, Anand; Dor, Frank J. M. F.; Papalois, Vassilios
Abstract : Introduction . We present our experience with hypothermic machine perfusion (HMP) versus cold storage (CS) in relation to kidney transplant outcomes. Methods . Retrospective analysis of 33 consecutive HMP kidney transplant outcomes matched with those of 33 cold stored: delayed graft function (DGF), length of hospital stay (LOS), estimated glomerular filtration rate (eGFR), and patient and graft survival were compared. Renal Resistive Indexes (RIs) during HMP in relation to DGF were also analysed. Results . In the HMP group, mean HMP time was 5.7 ± 3.9 hours with a mean cold ischaemic time (CIT) of 15 ± 5.6 versus 15.1 ± 5.3 hours in the CS group. DGF was lower in the HMP group (p=0.041), and donation after Circulatory Death (DCD) was a predictor for DGF (p<0.01). HMP decreased DGF in DCD grafts (p=0.036). Patient and graft survival were similar, but eGFR at 365 days was higher in the HMP cohort (p<0.001). RIs decreased during HMP (p<0.01); 2-hours RI ≥ 0.45 mmHg/mL/min predicted DGF in DCD kidneys (75% sensitivity, 80% specificity; area under the curve 0.78); 2-hours RI ≥ 0.2 mmHg/ml/min predicted DGF in DBD grafts (sensitivity 100%, specificity 91%; area under the curve 0.87). Conclusion . HMP decreased DGF compared to CS, offering viability assessment pretransplant and improving one-year renal function of the grafts.